Sintesis Nanopartikel Mg-CoFe3O4 dari Limbah Industri Ubin Keramik sebagai Material Fotokatalis - RIZKI ADITYAWAN MAULANA; EKO PRABOWO HADISANTOSO; RIZKY BERLIANA WIJAYANTI; FERRY ARIFIADI; KRISTANTO WAHYUDI (UIN Sunan Gunung Djati Bandung, 2022)
The ceramic industry produces iron oxide waste which can be used as a photocatalyst material to degrade methylene blue (MB) dye. Iron oxide waste mostly contains Fe2O3. In this study, Fe3O4 was synthesized from ceramic tile industrial waste with the addition of Na-Citra to reduce Fe2O3 to Fe3O4 using the solid state method. Fe3O4 (magnetite) material improved its photocatalytic performance by adding Mg2+ and Co2+ dopants to form MgxCo1-xFe3O4 (MCM) with a fraction x = 0.03; 0.05 and 0.07 are written as MCM-1, MCM-2, and MCM-3 by the solid state method. XRD results show that Fe3O4, MCM-1, MCM-2, MCM-3 have spinel cubic shape which is compatible with Fe3O4 phase and still contains Fe2O3 impurities. The crystal sizes obtained for Fe3O4, MCM-1, MCM-2, MCM-3 were 39.61; 34.42; 41.28; 32.11 nm. The smaller the crystal size, the better the photocatalyst degradation. SEM results showed that Fe3O4, MCM-1, MCM-2, and MCM-3 samples had a spherical cubic morphology and agglomeration occurred with particle sizes ranging from 126.05 to 149.50 nm. The SEM results show that the more Mg2+ added, the smaller the agglomeration that occurs. The results of UV-DRS show that the addition of Mg2+ dopants can reduce the band gap from 2.02 to 1.95 eV. With the results obtained, the material that has been successfully synthesized can be used as a photocatalyst material.